Privatization and efficiency: once upon a time in Libya / Mohamed Saad Mohamed Abokaresh, Badrul Hisham Kamaruddin, Rohani Mohd - Mohd, Rohani (Faculty of Business and Management, 2013)
This efficiency assessment of Libyan manufacturing firms is unique as efficiency is assessed on a developing country that undertakes privatization primarily for political and organizational reasons. Moreover, the state of mixed results in the literature with regards to production efficiency between state-owned and private owned firms motivated the conduct of this study. Despite deliberate implementation of programs to improve efficiency, the situation in Libya was such that firms were able to improve their performance through internal efforts even in a negative environment. This has made the results of this study differ for developed and developing countries. For instance, from 1978-2002, the socialism-oriented economy replaced the capitalism system, transferring private ownership to the state. This has resulted in low levels of labour productivity, and weak structure of production in terms of acquisition of new technology. Moreover, both the United States and United Nation Security Council imposed sanctions on Libya from 1992-2003 which have restricted foreign direct investments. During these periods, the Libyan manufacturing sector suffered from increasing inefficiencies resulting in slowing down of growth of output following decline in labour productivity and financial capital. The objective of this study is to compare the technical efficiency of firms before and after privatization to be able to differentiate between state control and privatized firms, as well. Data Envelopment Analysis (DEA) technique was used to compute the efficiency scores of firms. The average efficiency score before privatization was 49.5 per cent, but the score improved to 62.3 per cent after privatization. However, this minor improvement was not statistically significant as verified by the Mann-Whitney U test. These results have verified the situations in Libya which suggest that firms in Libya have not been prepared for real privatization. Consequently, almost all firms faced difficulties in optimizing their own resources economically